Neurological Consequences of SARS-CoV-2 Infection and Concurrence of Treatment-Induced Neuropsychiatric Adverse Events in COVID-19 Patients: Navigating the Uncharted - Borah, Pobitra; Deb, Pran Kishore; Chandrasekaran, Balakumar; Goyal, Manoj; Bansal, Monika; Hussain, Snawar; Shinu, Pottathil; Venugopala, Katharigatta N.; Al-Shar’i, Nizar A.; Deka, Satyendra; Singh, Vinayak (Frontiers in Molecular Biosciences, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) binds to the angiotensin-converting enzyme 2 (ACE2) receptor and invade the human cells to cause COVID-19-related pneumonia. Despite an emphasis on respiratory complications, the evidence of neurological manifestations of SARS-CoV-2 infection is rapidly growing, which is substantially contributing to morbidity and mortality. The neurological disorders associated with COVID-19 may have several pathophysiological underpinnings, which are yet to be explored. Hypothetically, SARS-CoV-2 may affect the central nervous system (CNS) either by direct mechanisms like neuronal retrograde dissemination and hematogenous dissemination, or via indirect pathways. CNS complications associated with COVID-19 include encephalitis, acute necrotizing encephalopathy, diffuse leukoencephalopathy, stroke (both ischemic and hemorrhagic), venous sinus thrombosis, meningitis, and neuroleptic malignant syndrome. These may result from different mechanisms, including direct virus infection of the CNS, virus-induced hyper-inflammatory states, and post-infection immune responses. On the other hand, the Guillain-Barre syndrome, hyposmia, hypogeusia, and myopathy are the outcomes of peripheral nervous system injury. Although the therapeutic potential of certain repurposed drugs has led to their off-label use against COVID-19, such as anti-retroviral drugs (remdesivir, favipiravir, and lopinavir-ritonavir combination), biologics (tocilizumab), antibiotics (azithromycin), antiparasitics (chloroquine and hydroxychloroquine), and corticosteroids (dexamethasone), unfortunately, the associated clinical neuropsychiatric adverse events remains a critical issue. Therefore, COVID-19 represents a major threat to the field of neuropsychiatry, as both the virus and the potential therapies may induce neurologic as well as psychiatric disorders. Notably, potential COVID-19 medications may also interact with the medications of pre-existing neuropsychiatric diseases, thereby further complicating the condition. From this perspective, this review will discuss the possible neurological manifestations and sequelae of SARS-CoV-2 infection with emphasis on the probable underlying neurotropic mechanisms. Additionally, we will highlight the concurrence of COVID-19 treatment-associated neuropsychiatric events and possible clinically relevant drug interactions, to provide a useful framework and help researchers, especially the neurologists in understanding the neurologic facets of the ongoing pandemic to control the morbidity and mortality.